Evaluation of multistory buildings using performance-based seismic in life safety level - Ahmadi, Mohammad (2015)
In recent decade, performance-based seismic design (PBSD) is becoming a popular method allover the world. Based on this method, life safety level is a target performance for most of the building. Lack of defmed distance between each level of performance and performance point is the main shortcoming upon which this study was initiated. In this regard, five RC frames were analyzed by ETABS to investigate the effect of shear wall on material consumption in terms of life safety leveL In addition, to connect performance point to structural damages, effect of different concrete compressive strength on static damage index was assessed. Besides, two experimental 1/4 scaled frames with single degree of freedom (SDOF) and the second frame has smaller beam size than the first frame were constructed and tested under semi-cyclic load to validate ETABS pushover curve. Semi-cyclic curve and its smoothed curve, cracks penetration patterns and plastic hinge formation sequence were proposed to acquire experimental findings. Moreover, two numerical scaled models with (same experimental frame size) were analyzed; first is by hinge by hinge method using MATLAB and second is by ABAQUS to verify the experimental results. This study has proposed performance factor to specify life safety performance level which is equal to 80%. According to this investigation and analysis of multistory RC frames by ETABS, it was found that shear wall decreases concrete and steel bars consumption of 12% and 32%, respectively in terms of life safety leveL It was also found that low concrete compressive strength will significantly increase the static damage index especially in high-rise buildings, e.g. for 10 story frames by reducing 10 MPa, static damage index has been increased by 11%. The experimental results indicate that the smaller beam size enhances energy dissipation by 40%. These findings are clearly supported by ABAQUS and ETABS results. The experimental has also shown that the plastic hinge starts from beam and gradually propagates into columns and this achievement certified by the proposed hinge by hinge method.